Modeling and experimental identification of drill string torsional dynamics under uncertainties - Real, Fabio Ferreira (2020)
Submitted by Daniele Fonseca (daniele@ct.ufrj.br) on 2020-05-06T01:51:36Z No. of bitstreams: 1 FabioFerreiraReal.pdf: 16565569 bytes, checksum: 5c3523887da61381bf24b6276fb9474f (MD5)